World experience in organizing deposit guarantee systems - Vorobуeva, S.M. (KSU Publ., 2020)
Object: To identify possible ways to improve the deposit insurance system in the Republic of Kazakhstan on the basis of studying the world practice of deposit insurance and identifying the functioning of various models of deposit insurance systems. Methods: Used such basic methods of cognition as the method of description and comparison, periodization, generalization and logical analysis. Results: A retrospective review of the establishment of deposit insurance systems in different countries of the world and integration associations was carried out, differences in the organization of deposit insurance according to the American and continental models were identified, suggestions were made for further improvement of the practice of deposit insurance in the Republic of Kazakhstan. Conclusions: The author defines further directions for the development of the global practice of deposit insurance by unifying deposit guarantee systems and the emergence of superstructure deposit protection systems within integration associations and the functioning of cross-border insurance systems. Based on international experience, the author formulated a conclusion about the need to change the legislative conditions for guaranteeing deposits in the Republic of Kazakhstan in terms of recognition by entities of the deposit insurance system of non-bank organizations, the extension of insurance liability to deposits of legal entities, and increasing the maximum security for guaranteed deposits. The author proposes a change in the practice of forming a deposit guarantee fund in order to improve the conditions for participation in the deposit guarantee system for second-tier banks.
Салымдарға кепілдік беру жүйесін ұйымдастырудың əлемдік тəжірибесі
Мировой опыт организации систем гарантирования вкладов
Keywords: world models of deposit insurance systems; unification of deposit insurance systems; mandatory deposit guarantee system; deposit guarantee fund; financing methods; objects and subjects of deposit insurance; maximum insurance coverage